Bi-specific molecule against EGFR and death receptors simultaneously targets proliferation and death pathways in tumors - Yanni Zhu (Nature Portfolio, 2017)
Abstract Developing therapeutics that target multiple receptor signaling pathways in tumors is critical as therapies targeting single specific biomarker/pathway have shown limited efficacy in patients with cancer. In this study, we extensively characterized a bi-functional molecule comprising of epidermal growth factor receptor (EGFR) targeted nanobody (ENb) and death receptor (DR) targeted ligand TRAIL (ENb-TRAIL). We show that ENb-TRAIL has therapeutic efficacy in tumor cells from different cancer types which do not respond to either EGFR antagonist or DR agonist monotherapies. Utilizing pharmacological inhibition, genetic loss of function and FRET studies, we show that ENb-TRAIL blocks EGFR signalling via the binding of ENb to EGFR which in turn induces DR5 clustering at the plasma membrane and thereby primes tumor cells to caspase-mediated apoptosis. In vivo, using a clinically relevant orthotopic resection model of primary glioblastoma and engineered stem cells (SC) expressing ENb-TRAIL, we show that the treatment with synthetic extracellular matrix (sECM) encapsulated SC-ENb-TRAIL alleviates tumor burden and significantly increases survival. This study is the first to report novel mechanistic insights into simultaneous targeting of receptor-mediated proliferation and cell death signaling pathways in different tumor types and presents a promising approach for translation into the clinical setting.